Early Warning Method and Fire Extinguishing Technology of Lithium-Ion Battery Thermal Runaway: A Review - Kuo Wang; Dongxu Ouyang; Xinming Qian; Shuai Yuan; Chongye Chang; Jianqi Zhang; Yifan Liu (Energies, 2023)
Lithium-ion batteries (LIBs) are widely used in electrochemical energy storage and in other fields. However, LIBs are prone to thermal runaway (TR) under abusive conditions, which may lead to fires and even explosion accidents. Given the severity of TR hazards for LIBs, early warning and fire extinguishing technologies for battery TR are comprehensively reviewed in this paper. First, the TR reaction mechanism and hazards of LIBs are discussed. Second, the TR early warning and monitoring methods of LIBs are summarized in five aspects consisting of acoustic, heat, force, electricity, and gas. In addition, to reduce the fire and explosion hazards caused by the TR of LIBs, the highly efficient extinguishing agents for LIBs are summarized. Finally, the early warning technology and fire extinguishing agent are proposed, which provides a reference for the hazard prevention and control of energy storage systems.